2008
DOI: 10.1080/15287390801997732
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Public Health: A Guidance Document for Risk Managers

Abstract: This guidance document is a reference for air quality policymakers and managers providing state-of-the-art, evidence-based information on key determinants of air quality management decisions. The document reflects the findings of five annual meetings of the NERAM (Network for Environmental Risk Assessment and Management) International Colloquium Series on Air Quality Management (2001-2006), as well as the results of supporting international research. The topics covered in the guidance document reflect critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 194 publications
3
70
0
Order By: Relevance
“…Health effects have been associated predominately with at least one of the so-called criteria pollutants that are routinely measured to assess air quality in most cities around the world. Ozone and PM represent a common persistent problem in several cities, with important effects on public health (Craig et al, 2008). Although recent attention has been brought towards understanding the role of multipollutants interactions in air pollution related health effects (Mauderly and Samet, 2009), current methodological approaches have focused on ozone (Samoli et al, 2009) and, more importantly, in PM as the criteria pollutant with stronger associations with most of the described health effects.…”
Section: Health Studiesmentioning
confidence: 99%
“…Health effects have been associated predominately with at least one of the so-called criteria pollutants that are routinely measured to assess air quality in most cities around the world. Ozone and PM represent a common persistent problem in several cities, with important effects on public health (Craig et al, 2008). Although recent attention has been brought towards understanding the role of multipollutants interactions in air pollution related health effects (Mauderly and Samet, 2009), current methodological approaches have focused on ozone (Samoli et al, 2009) and, more importantly, in PM as the criteria pollutant with stronger associations with most of the described health effects.…”
Section: Health Studiesmentioning
confidence: 99%
“…The other studies have shown that reductions in life expectancy of 1.11 years in the Netherlands, 1.37 years in Finland, and 0.80 year in Canada resulting from increases in ambient PM 2.5 concentrations of 10 µg/m 3 [20,21]. Longterm exposure to PM is particularly damaging to human health and reduces life expectancy, that is why reducing long-term PM concentrations and exposure is a priority [21,22].…”
Section: Relation Between Air Pollution and Life Expectancy (Lle)mentioning
confidence: 99%
“…30 Among the environmental exposures that may induce inflammation and oxidative stress leading to central nervous system pathology, air pollution may be considered as the most prevalent source. 31 The 2 possible pathways in which PM can affect neurocognitive function are (1) oxidative stress induced by respiratory intake of PM and the penetration of the inflammatory compounds into the blood-brain barrier 32 ; (2) direct entry of PM into the central nervous system through the olfactory bulb.…”
Section: Biological Mechanismmentioning
confidence: 99%